Factor on food heritage awareness among young generation in malaysia - Rasyidah Nurain Noredzuan; Nursyuhada Anis Md Shaharon; Siti Nur Amirah Ismail@Hassan; Sharmitha Arivananthan; Yusuffizairi Abdul Aziz (2022)
Heritage food is basically food that has been traditionalized by the process of lineage being passed down by ancestors of a clan to the next generation. In a multi-racial country like Malaysia, food has been the one of its cultural identities where it is infused by the multi-race of Malays, Chinese and Indians. Our study is to identify the relationship between level of awareness, knowledge, and perspective of food heritage to the younger generation. The Malaysian traditional food preference customs are swiftly risen as it has commercialized compilations of food in modern day society among the younger generations. Therefore, considerations that concerns the country’s ethnicity tradition culinary awareness and transmission whether tangible knowledge is to be passed down to the younger generation.